ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENDAPATAN NEGARA BUKAN PAJAK (PNBP) PADA KANTOR KEJAKSAAN NEGERI PANGKALPINANG - Kurnia, Evi; Tri Setyo Mulyani, Hendarti; Ruben Manullang, Rizal (Jurnal Ilmiah Niaga Bisnis Elektronik, 2022)
This study aims to analyze the level of effectiveness and contribution of the types of Non-Tax State Revenue at the Kejaksaan Negeri Pangkalpinang Pangkalpinang from 2019 to 2021. This research uses a quantitative descriptive analysis method. The object of this research is the types of non-tax state income. The data used in this study is data in the form of the State Revenue and Grants Budget Realization Report from 2019 to 2021. The results of this study indicate that the effectiveness of the total Non-Tax State Revenue (PNBP) studied in 2019 to 2021 the level of effectiveness has exceeded 100%, which means that the Kejaksaan Negeri Pangkalpinang Pangkalpinang ability to carry out its duties and functions as an Agency/Institution that generates Non-Tax State Revenue (PNBP) has been very effective. The contribution of the types of Non-Tax State Revenue (PNBP) to Non-Tax State Revenue (PNBP) from 2019 to 2022 is still not evenly distributed, the type of Non-Tax State Revenue (PNBP) with good criteria consists of Revenue from Sales of confiscated goods which has been decided/determined by the court with a contribution of 46.49% in 2019 and Traffic Fine Income with a contribution of 40.76% in 2020 while other types of Non-Tax State Revenue (PNBP) contribute below 40% with the criteria moderate, low and very low.